PENINGKATAN KAPASITAS ANGGOTA DPRD KABUPATEN CILACAP DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Alizar Isna (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
One of the functions of the DPRD is the legislative function, which includes the preparation and stipulation of Regional Regulations (Raperda) for the Regional Revenue and Expenditure Budget (APBD). In order to increase the capacity of DPRD members in the legislative function, the Cilacap Regency DPRD held training which was packaged in the form of an Academic Study of the 2024 Regional Revenue and Expenditure Budget (APBD) Draft Regional Regulations (Raperda). The training used 2 learning methods, namely varied lectures and hypothetical situation techniques. , one of which discusses the material